Penggunaan Internet Dalam Mengembangkan Metode Pengajaran Untuk Guru-Guru di Kelurahan Rawa Buaya Jakarta Barat - Hirdinis M; Nuryadi Hasan; Suprapto Suprapto (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2019)
The aim of this Community Service activity is for teachers to be able to use and utilize the internet optimally to develop teaching methods effectively. The training was attended by 10 participants and 2 participants did not complete the training because there were assignments from the school. The number of participants in this training is limited because the members of the implementation team, facilities and infrastructure are limited. The training material is the introduction of the internet to develop teaching methods, the target of the activity is the teachers in the West Jakarta Rawa Buaya Village. Activities carried out by lecture, demonstration and hands-on method with technical guidance. Participants are guided to upload and download, and browse. The participants then exchanged e-mail addresses and conducted correspondence via e-mail, browsing and downloading certain subject matter. The equipment used in this training activity is a computer connected to the Internet for the means of opening PPT program files, Infocus for and Cameras to cover and document photographs in the form of activities carried out.